Evaluation of broiler dark house illumination systems, with and without thermal insulation (Research, Society and Development, 2021)
In the breeding of broiler house, the proper use of lighting systems has great influence on the welfare and the productivity of the birds. The objective was to evaluate two artificial lighting systems used in broiler house in terms of the allocative efficiency of luminance. One of the broiler house was closed with black raffia bag (dark house), without thermal insulation (NTI) and its lighting was composed of incandescent, compact fluorescent light (LFCs) and light emitting diode (LED) bulbs. The other broiler house was closed with extruded polystyrene panels (XPS) and thermally insulated (TI), and its lighting was composed of compact fluorescent lamps. The influence of external light of sun inside the broiler house was analyzed by means of exhaust holes and the degree of distribution of illumination through statistical analyzes and the study of the distribution uniformity coefficient (DUC). Contour maps were prepared showing the degree of internal luminance distribution for each broiler house, specifically in the area that did not suffer interference from external natural sunlight. The results showed that natural lighting influenced the internal lighting across the last 18 meters at the end of the broiler house and there was a more homogeneous lighting in the broiler house TI.